Potential valorization of by-product materials from oil palm: A review of alternative and sustainable carbon sources for carbon-based nanomaterials synthesis - Salisu Nasir; Mohd Zobir Hussein; Zulkarnain Zainal; Nor Azah Yusof; Syazwan Afif Mohd Zobir; Ibrahim Mustapha Alibe (BioResources)
The crises in global energy and environmental degradation, combined with developing consumer demands have stimulated researchers’ interest in inexpensive, environmentally friendly functional materials. Based on a projected annual production of palm oil in Malaysia of over 15.4 million metric tons by 2020, it is estimated that about 46.6 tons of lignocellulosic wastes will be generated. Transforming these wastes into wealth could be integrated into a global paradigm shift towards sustainable development. Carbon-based nanomaterials including graphene, graphene oxide, carbon nanotubes, epoxy nanocomposites, porous carbon nanoparticles, and nanoactivated carbons-filled-epoxy nanocomposites have been produced from these by-product materials using methods such as vapour deposition, pyrolysis, hydrolysis, chemical composition, high energy ball milling, and solution casting. This review attempts to present the current developments on renewable carbon nanomaterials derived from oil palm-based precursors with some insights given on their potential applications as energy storage materials.